Forensic evidence in proving crimes: Exploring the legal frameworks of Sharīʿah = Bukti forensik bagi membuktikan jenayah: Menerokai rangka kerja guaman Sharīʿah - Gilani, Sayyid Muhammad Yunus; Shalim, K. M. Zakir Hossain Shalim (International Islamic University Malaysia, 2016)
Forensic evidence is an evolving science in the field of criminal investigation and prosecutions. It has been widely used in the administration of justice in the courts and the Western legal system, particularly in common law. To accommodate this new method of evidence in Islamic law, this article firstly, conceptualizes forensic evidence in Islamic law. Secondly, explores legal frameworks for its adoption in Islamic law.